The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.7554/elife.59119
|View full text |Cite
|
Sign up to set email alerts
|

Bardet–Biedl syndrome 3 protein promotes ciliary exit of the signaling protein phospholipase D via the BBSome

Abstract: Certain ciliary signaling proteins couple with the BBSome, a conserved complex of Bardet-Biedl syndrome (BBS) proteins, to load onto retrograde intraflagellar transport (IFT) trains for their removal out of cilia in Chlamydomonas reinhardtii. Here, we show that loss of the Arf-like 6 (ARL6) GTPase BBS3 causes the signaling protein phospholipase D (PLD) to accumulate in cilia. Upon targeting to the basal body, BBSomes enter and cycle through cilia via IFT, while BBS3 in a GTP-bound state separates from BBSomes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(100 citation statements)
references
References 62 publications
6
86
0
Order By: Relevance
“…The IFT-B complex contains 16 subunits and mediates anterograde (ciliary base-to-tip direction) trafficking of proteins driven by heterotrimeric kinesin-II, and the IFT-A complex comprises six subunits and mediates retrograde trafficking driven by the dynein-2 motor complex [12,13]. Besides these roles, the IFT-B complex participates in the export of membrane proteins across the ciliary gate in conjunction with the BBSome, which is composed of eight proteins encoded by the causative genes of Bardet-Biedl syndrome (BBS) [14][15][16][17][18]. On the other hand, the IFT-A complex mediates the import of membrane proteins with the aid of the TULP3 adaptor protein [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The IFT-B complex contains 16 subunits and mediates anterograde (ciliary base-to-tip direction) trafficking of proteins driven by heterotrimeric kinesin-II, and the IFT-A complex comprises six subunits and mediates retrograde trafficking driven by the dynein-2 motor complex [12,13]. Besides these roles, the IFT-B complex participates in the export of membrane proteins across the ciliary gate in conjunction with the BBSome, which is composed of eight proteins encoded by the causative genes of Bardet-Biedl syndrome (BBS) [14][15][16][17][18]. On the other hand, the IFT-A complex mediates the import of membrane proteins with the aid of the TULP3 adaptor protein [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Arf family GTPases associate with the inner membrane via its N-terminal amphipathic helix (Amor et al, 1994;Liu et al, 2010;Zhang et al, 2011b) and their N-terminal 15 residues are found essential for this association (Jin et al, 2010;Liu et al, 2021;Mourão et al, 2014). They were further reported to anchor to the membrane through myristylation on their glycine residue at the second amino acid position and disruption of myristylation by introducing a G2A mutation fully prevents them from associating with the membrane (Fig.…”
Section: Arl3 Gdp Requires Its N-terminal 15 Amino Acids and The G2 Residue For Membrane Association And Diffusion Into Ciliamentioning
confidence: 99%
“…In this study, we identified the BBSome acts as a major ARL3 effector at the ciliary base right above the TZ but not in the cell body of C. reinhardtii. ARL3 mimics other Arf-like GTPases for diffusing into cilia and reversibly binding the ciliary membrane via its N-terminal amphipathic helix and the G2 residue but in a GDP-dependent manner (Liu et al, 2021). Once in cilia, ARL3 undergoes GTPase cycling and the activated ARL3 GTP binds the retrograde IFT-detached and PLD-laden BBSome at the proximal ciliary region right above the TZ and recruits it to diffuse through the TZ for ciliary retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…With small GTPases, the BBSome assembles into a coat that traffics Golgi vesicles with their valuable cargo to the IFT apparatus where some of the cargo is inserted into the ciliary membrane [36][37][38][39]. G protein coupled protein receptors, such as somatostatin receptor 3 [37] and neuropeptide Y [40], depend upon the BBSome for ciliary localization while other proteins like the signaling protein Phospholipase D depend upon the function of the BBSome to exit the cilium [24,25,41]. Overall, the BBSome has a lot of sway over the ciliary membrane proteome.…”
Section: Bbs Proteinsmentioning
confidence: 99%
“…As discussed above, for some proteins meeting up with IFT trains for entry into the cilium can be orchestrated by the BBSome [36][37][38][39]. Other proteins require the BBSome to pass back through the transition zone to exit the cilium [24,25,41].…”
Section: Transition Zonementioning
confidence: 99%